Dysregulated non-coding telomerase RNA component and associated exonuclease XRN1 in leucocytes from women developing preeclampsia-possible link to enhanced senescence - T. Lekva (Nature Portfolio, 2021)
Abstract Senescence in placenta/fetal membranes is a normal phenomenon linked to term parturition. However, excessive senescence which may be induced by telomere attrition, has been associated with preeclampsia (PE). We hypothesized that the telomerase complex in peripheral blood mononuclear cells (PBMC) and circulating telomere associated senescence markers would be dysregulated in women with PE. We measured long non-coding (nc) RNA telomerase RNA component (TERC) and RNAs involved in the maturation of TERC in PBMC, and the expression of TERC and 5′–3′ Exoribonuclease 1 (XRN1) in extracellular vesicles at 22–24 weeks, 36–38 weeks and, 5-year follow-up in controls and PE. We also measured telomere length at 22–24 weeks and 5-year follow-up. The circulating senescence markers cathelicidin antimicrobial peptide (CAMP), β-galactosidase, stathmin 1 (STMN1) and chitotriosidase/CHIT1 were measured at 14–16, 22–24, 36–38 weeks and at 5-year follow-up in the STORK study and before delivery and 6 months post-partum in the ACUTE PE study. We found decreased expression of TERC in PBMC early in pregnant women who subsequently developed PE. XRN1 involved in the maturation of TERC was also reduced in pregnancy and 5-year follow-up. Further, we found that the senescence markers CAMP and β-galactosidase were increased in PE pregnancies, and CAMP remained higher at 5-year follow-up. β-galactosidase was associated with atherogenic lipid ratios during pregnancy and at 5-year follow-up, in PE particularly. This study suggests a potential involvement of dysfunctional telomerase biology in the pathophysiology of PE, which is not restricted to the placenta.